2017
DOI: 10.1371/journal.pbio.2002266
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the tardigrades Hypsibius dujardini and Ramazzottius varieornatus

Abstract: Tardigrada, a phylum of meiofaunal organisms, have been at the center of discussions of the evolution of Metazoa, the biology of survival in extreme environments, and the role of horizontal gene transfer in animal evolution. Tardigrada are placed as sisters to Arthropoda and Onychophora (velvet worms) in the superphylum Panarthropoda by morphological analyses, but many molecular phylogenies fail to recover this relationship. This tension between molecular and morphological understanding may be very revealing o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
347
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 202 publications
(367 citation statements)
references
References 120 publications
(199 reference statements)
17
347
1
2
Order By: Relevance
“…Other animals and other eukaryotes are regularly reported to have 1–2% LGT in their genomes based on what appear to be widely accepted analytical tools. My point is this: If eukaryote LGT is occurring in nature at a rate that leads to an LGT content of 1–2% per genome, where are the cumulative effects? Why does it not accrue along lineages?…”
Section: In the Beginning There Was The Human Genome…mentioning
confidence: 99%
“…Other animals and other eukaryotes are regularly reported to have 1–2% LGT in their genomes based on what appear to be widely accepted analytical tools. My point is this: If eukaryote LGT is occurring in nature at a rate that leads to an LGT content of 1–2% per genome, where are the cumulative effects? Why does it not accrue along lineages?…”
Section: In the Beginning There Was The Human Genome…mentioning
confidence: 99%
“…A key pillar of Martin's argument is that the rate of eukaryote LGTs into specific lineages cannot be as high as estimated, otherwise the cumulative effects of these LGTs should be significant and readily detectable. To illustrate this point, Martin discusses LGTs inferred in the genomes of 12 Drosophila species by Yoshida et al He argues their estimates of LGT are too high, stating: “I find claims of 0.5% LGT per fly genome very difficult to digest.” However, Yoshida et al never made any such claim. They estimated LGT by flagging genes in a given Drosophila genome that displayed substantially greater similarity to non‐metazoan versus metazoan homologs.…”
Section: Are Estimated Frequencies Of Lgt Too High?mentioning
confidence: 99%
“…The DSBs induced by prolonged desiccation were suggested to open the "gateway to genetic exchange" and account for the elevated HGT frequency in bdelloid rotifers Boschetti, et al 2012;Flot, et al 2013;Hespeels, et al 2014;Eyres, et al 2015;Debortoli, et al 2016). However, the DSBs induced by prolonged desiccation in tardigrades (Neumann, et al 2009) did not result in an elevated level of HGTs (Yoshida, et al 2017). We first examine whether there are elevated levels of endosymbiotic DNA transfers (EDTs) in the desiccation-tolerant bdelloid rotifers and tardigrades.…”
Section: Numts/nuptsmentioning
confidence: 99%
“…The first analysis of a tardigrade draft genome (Hypsibius dujardini) suggested more extensive HGTs than bdelloid rotifers, 17.5% of its genes were identified as foreign genes originated from bacteria, plants, fungi, and archaea (Boothby, et al 2015). However, subsequent independent sequencing of the same species as well as another tardigrade species, Ramazzottius varieornatus, consistently showed that the percentage of foreign genes in tardigrades is much lower, with 2.3% as the reported upper bound (Arakawa 2016;Bemm, et al 2016;Delmont and Eren 2016;Hashimoto, et al 2016;Koutsovoulos, et al 2016;Yoshida, et al 2017). Most previously identified foreign genes should result from contamination of DNA from non-target organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation